The resistance of cocoa hybrids to vascular-streak dieback - Agung Wahyu Soesilo; Indah Anita-Sari (Indonesian Coffee and Cocoa Research Institute, 2011)
Breeding for VSD resistance on cocoa was carried out by inter-crossing the selected clones of TSH 858, KW 162, KW 163, KW 165, KEE 2, ICS 13 and NIC 7 which were selected based on the criteria of VSD resistance, productivity and cross-compatibility. This research has objective to evaluate hybrids of the crossess for VSD resistance, inheritance of the resistance and selecting the most valuable parental-clones for further crossess. Fourteen hybrids and one control were tested 14 in the randomized-completely block design with 4 blocks where in each plot 16 trees planted at Kaliwining Experimental Station in Jember. The resistance was evaluated in the field by scoring the symptoms in the range of 0—6 at 7 year after planting. The scores were varied significantly among the hybrids in the range of 2.19—4.53. Hybrids which were generated from the crosses of resistant clones performed lower number of the score than the hybrids generated from crosses between two susceptible clones (TSH 858 x NIC 7) which performed highest score. The hybrids classified as resistant were TSH 858 x KW 162 (F1 and reciprocal), KW 162 x KEE 2 (F1 and reciprocal), KW 162 x ICS 13, KW 165 x KEE 2. Of the parental clones, KW 162 is the most promising parent as lower score obtained when used it as male or female compared to KEE 2 which performed quite similar of the score with TSH 858 as susceptible parent. Therefore, it could be supposed that KW 162 has better combining ability than KEE 2 where these resistant-clones showed different segregation of their resistance. The resistance was segregated by KW 162 in term of ratio 15 resistant : 1 susceptible while KEE 2 the ratio 1 resistant: 1 susceptible.Key words: Theobroma cocoa L., hybrid, resistance, vascular-streak dieback.